The Future of Representative Democracy - Alonso, Sonia (Alonso Saenz de Oger); Keane, John (John Charlick), 1949-; Merkel, Wolfgang, 1952-; Fotou, Maria (Cambridge ; New York : Cambridge University Press, 2011)
"The Future of Representative Democracy poses important questions ab out representation, representative democracy and its future. Inspired b y the last major investigation of the subject by Hanna Pitkin over four decades ago, this ambitious volume fills a major gap in the literature by examining the future of representative forms of democracy in terms of present-day trends and past theories of representative democracy. Aw are of the pressing need for clarifying key concepts and institutional trends, the volume aims to break down barriers among disciplines and to establish an interdisciplinary dialogue among scholars. The contributo rs emphasise that representative democracy and its future is a subject of pressing scholarly concern and public importance. Paying close atten tion to the unfinished, two-century-old relationship between democracy and representation, this book offers a fresh perspective on current pro blems and dilemmas of representative democracy and the possible future development of new forms of democratic representation"--
Editors' introduction: Rethinking the future of representative democ racy / Sonia Alonso, John Keane and Wolfgang Merkel -- 1. Repr esentative democracy and its critics / Nadia Urbinati -- 2. Re presentative democracy and the populist temptation / Klaus von Beyme -- 3. The wider canvas: representation and democracy in state an d society / Michael Saward -- 4. Performance and deficits of p resent-day representation / Bernhard Wessels -- 5. Do parliame nts have a future? / David Beetham -- 6. Engendering represent ative democracy / Drude Dahlerup -- 7. Representative democrac y and the multinational demos / Sonia Alonso -- 8. Diagnosing and designing democracy in Europe / Philippe Schmitter -- 9. Moni tory democracy? / John Keane -- 10. Representing nature / R obyn Eckersley -- 11. Democracy and representation beyond the nat ion state / Michael Zèurn and Gregor Walter-Drop.
Includes bibliographical references (pages 282-301) and index.
Keywords: Representative government and representation; Democracy